REFERENCES AND CONJUNCTIONS AS MARKERS OF PROPOSITIONAL RELATIONS IN DISCOURSE SEMANTICS - Harris Hermansyah Setiajid (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2022)
Discourse is the most fundamental linguistic unit that is commonly used in daily life. To compose an effective discourse, one needs a mechanism for combining the discourse's propositions. The technique is referred to as a proposition relational marker. The tool's format, which includes references and conjunctions. The term "reference" refers to propositions in a discourse, whereas "conjunction" refers to propositions in a discourse. The purpose of this article is to explain the comprehension, meaning, and application of references and conjunctions.